Non-volatile and volatile composition of West African bulk and Ecuadorian fine-flavor cocoa liquor and chocolate. (April 2020) - Tuenter, Emmy; Delbaere, Claudia; De Winne, Ann; Bijttebier, Sebastiaan; Custers, Deborah; Foubert, Kenn; Van Durme, Jim; Messens, Kathy; Dewettinck, Koen; Pieters, Luc
Graphical abstract: Highlights: In-depth study of the composition of a bulk and a fine-flavor cocoa liquor and chocolate. Investigation of volatile (HS-SPME GC–MS) and non-volatile metabolites (UPLC-HRMS). A wide range of non-volatile compounds, both polyphenols and non-phenolic compounds, could be identified and quantified. Principal component analysis revealed the main distinctive (non-)volatile constituents. The suggested approach results in a thorough comparison of cocoa samples. Abstract: Cocoa products are obtained from the seeds of Theobroma cacao L. In this research, cocoa liquor and chocolate produced from cocoa beans from West Africa (Forastero, "bulk" cacao) and Ecuador (Nacional variety, "fine-flavor" cacao), were investigated, using a novel approach in which various analytical techniques are combined in order to obtain in-depth knowledge of the studied cocoa samples. The levels of various classes of primary metabolites were determined and a wide range of secondary metabolites, including volatile organic acids, aldehydes, esters, pyrazines, polyphenols, methylxanthines and biogenic amines, were identified and/or quantified by HS-SPME GC–MS (headspace-solid phase microextraction gas chromatography - mass spectrometry). and UPLC-HRMS (ultra-performance liquid chromatography - high resolution mass spectrometry). Odor Activity Values (OAV) were calculated to assess the contribution of individual volatiles on the final aroma. Various volatile aroma compounds were more abundant in the West African cocoa liquor and chocolate, while the Ecuadorian samples were richer in most quantified non-volatile metabolites. Principal component analysis (PCA) confirmed that the four samples can be clearly distinguished. Alcohols, pyrazines, amino acids and biogenic amines were found to be highly influential in causing this differentiation. The proposed approach can be useful in future studies on more extensive cocoa sample collections, in order to highlight similarities and pinpoint typical differences in chemical composition among these samples.